Does a Federal Country Need Federal Transfers when it has Labor Mobility? - Ferreira-Lopes, A.; Sequeira, T. N. (Regional Studies, 2010)
Does a federal country need federal transfers when it has labour mobility?, Regional Studies. This work empirically tests optimum currency area theory for members of a given monetary union (the United States). The United States is recognized as a country where labour mobility between states is high. This paper jointly assesses the consequences of having federal transfers and labour mobility in terms of the states' cyclical output. It is concluded that federal transfers undoubtedly contribute to increase cyclical output. However, out-migration may increase or decrease cyclical output, depending on certain conditions. As federal transfers proved to be much more important than migration, the answer to the question in the paper's title is ‘yes’.